2005
DOI: 10.1038/sj.jcbfm.9600217
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Stroke Induces Massive, Rapid Activation of the Peripheral Immune System

Abstract: Clinical experimental stroke induces injurious local brain inflammation. However, effects on the peripheral immune system have not been well characterized. We quantified mRNA and protein levels for cytokines, chemokines, and chemokine receptors (CCR) in brain, spinal cord, peripheral lymphoid organs (spleen, lymph node, blood, and cultured mononuclear cells from these sources), and blood plasma after reversible middle cerebral artery occlusion (MCAO) or sham treatment in male C57BL/6 mice. Middle cerebral arte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
472
1
5

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 484 publications
(507 citation statements)
references
References 38 publications
23
472
1
5
Order By: Relevance
“…We previously reported that focal cerebral ischemia in immunologically intact C57BL/6 mice resulted in a marked reduction in spleen cell numbers when evaluated at 22 h postischemia (1673 million in MCAO versus 3575 million in sham versus 9178 million in naïve mice; Offner et al, 2006). We show here that naïve SCID mice have drastically reduced splenocyte numbers (2.771.4 million cells, Table 1) as would be expected in the absence of T and B cells.…”
Section: Middle Cerebral Artery Occlusion-induced Changes In the Splesupporting
confidence: 63%
See 1 more Smart Citation
“…We previously reported that focal cerebral ischemia in immunologically intact C57BL/6 mice resulted in a marked reduction in spleen cell numbers when evaluated at 22 h postischemia (1673 million in MCAO versus 3575 million in sham versus 9178 million in naïve mice; Offner et al, 2006). We show here that naïve SCID mice have drastically reduced splenocyte numbers (2.771.4 million cells, Table 1) as would be expected in the absence of T and B cells.…”
Section: Middle Cerebral Artery Occlusion-induced Changes In the Splesupporting
confidence: 63%
“…Middle cerebral artery occlusion induced marked increases in secretion of inflammatory cytokines in spleens from intact WT mice at 6 and 22 h after occlusion (Offner et al, 2006). As is shown in Figure 2 (upper panel, filled bars), these changes at 22 h of MCAO were reflected by increased expression of mRNA for IFN-g, TNF-a, IL-6, MIP-2, IP-10, CCR1, and CCR2.…”
Section: Middle Cerebral Artery Occlusion-induced Changes In the Splementioning
confidence: 73%
“…Furthermore, using a cell culture model of human BBB established with relatively late passage endothelial cells and astrocytes, in this study only one factor, i.e., glucose, out of many involved in ischemic damage could be manipulated, whereas a number of pro-inflammatory cytokines and circulating components during an ischemic stroke, notably tumor necrosis factor-a, interleukin-6, vascular endothelial growth factor, and thrombin, are known to affect BBB permeability. 37,38 …”
Section: Discussionmentioning
confidence: 99%
“…The literature has consistently described stroke-induced early peripheral immune activation, which is defined by increased inflammatory cytokines in both experimental animal models and humans [10][11][12][13]. This early immune activation often progresses to immune suppression in patients with stroke.…”
Section: Impact Of Stroke On Immunitymentioning
confidence: 99%